2016
DOI: 10.1080/2162402x.2016.1239005
|View full text |Cite
|
Sign up to set email alerts
|

LAG-3 confers poor prognosis and its blockade reshapes antitumor response in head and neck squamous cell carcinoma

Abstract: Immunotherapy with immune checkpoint molecule-specific monoclonal antibody have obtained encouraging results from preclinical studies and clinical trials, which promoted us to explore whether this kind of immunotherapy could be applicable to head and neck squamous cell carcinoma (HNSCC). Lymphocyte activation gene-3 (LAG-3) is an immune checkpoint control protein that negatively regulates T cells and immune response. Here, using the human tissue samples, we report these findings that LAG-3 is overexpressed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
95
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 54 publications
12
95
0
Order By: Relevance
“…Moreover, we found high levels of LAG-3 + cells were independent predictor of poor OS and DFS. Similar to our result, high expression of LAG-3 predicted poor survival in head and neck squamous cell carcinoma [41], melanoma [37], soft tissue sarcomas [42] and nonsmall cell lung cancer(NSCLC) [40]. On the contrary, other studies in esophageal squamous cell carcinoma [43], breast cancers [39] and NSCLC [44]show the opposite results, and only one study in HCC has showed no prognostic significance [45].…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, we found high levels of LAG-3 + cells were independent predictor of poor OS and DFS. Similar to our result, high expression of LAG-3 predicted poor survival in head and neck squamous cell carcinoma [41], melanoma [37], soft tissue sarcomas [42] and nonsmall cell lung cancer(NSCLC) [40]. On the contrary, other studies in esophageal squamous cell carcinoma [43], breast cancers [39] and NSCLC [44]show the opposite results, and only one study in HCC has showed no prognostic significance [45].…”
Section: Discussionsupporting
confidence: 83%
“…Previous reports demonstrated that LAG‐3 was highly expressed on the surface of CD4 + CD25 high Foxp3 + Tregs in HNSCC and LAG‐3 blockade relieved the inhibitory function of Tregs (Jie et al., ). Consistent with these reports, another study found that LAG‐3 was upregulated on Tregs and inhibition of LAG3 decreased the population of immunosuppressive cells in HNSCC mouse models (Deng et al., ). The anti‐LAG3 blocking mAb, BMS‐986016, alone or in combination with nivolumab, has entered to phase I trial (NCT01968109) for solid tumors, including HNSCC.…”
Section: Lymphocyte‐activated Genesupporting
confidence: 58%
“…LAG‐3 (CD223), which is expressed on activated CD4 + and CD8 + T cells, NK cells, B cells, and plasmacytoid dendritic cells, is a co‐inhibitory immune checkpoint molecule (Deng et al., ). Although the known LAG‐3 ligand is the MHC II molecule, recent studies suggested that LSECtin molecule, which expressed in many tumors, may be another LAG‐3 ligand (Xu et al., ).…”
Section: Lymphocyte‐activated Genementioning
confidence: 99%
“…It was found that high checkpoint receptors expressed patients had a significantly shorter overall survival time in several malignancy . LAG‐3 and PD‐L1 have been confirmed as a prognostic factor independent of OSCC patients . TIM‐3 was reported to be upregulated in OSCC patients and associated with lymph node metastasis .…”
Section: Discussionmentioning
confidence: 97%
“…27 LAG-3 and PD-L1 have been confirmed as a prognostic factor independent of OSCC patients. 28 TIM-3 was reported to be upregulated in OSCC patients and associated with lymph node metastasis. 19 Increased expression of immunomodulator IDO was as- immunosuppressive microenvironment and combination therapy would be rational.…”
Section: Discussionmentioning
confidence: 99%